Anisotropia da irradiância solar difusa medida pelo método de sombreamento Melo-Escobedo: fatores de correção anisotrópicos e modelos de estimativa - Dal Pai, Alexandre [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
No presente trabalho é apresentado um modelo de correção anisotrópico para radiação difusa medida com anel de sombreamento Melo-Escobedo (ME) em função do índice de claridade (razão da radiação global pela extraterrestre). São propostos ainda dois modelos estatísticos da fração difusa isotrópica ( ) e anisotrópica ( ) em função do índice de claridade na estimativa das irradiações horária, diária e mensal. A base de dados das radiações global, direta na incidência e difusa medida pelo anel de sombreamento ME utilizada compreende o período de 1996 a 2002 monitorada pelo Laboratório de Radiometria Solar da UNESP/Botucatu/SP. O modelo de correção anisotrópico, obtido a partir das irradiâncias difusa medida pelo anel de sombreamento Melo-Escobedo (raio 40cm e largura 10cm) e medida pelo método da diferença (referência), considerou três intervalos discretos de por meio de três equações: (0 < < 0,30 - nublado); (0,30 < < 0,65 - parcialmente nublado); e (0,65 < < 1 - aberto). O modelo anisotrópico foi validado comparando-se a irradiância difusa anisotrópica estimada com a irradiância difusa de referência numa base de dados independente, mostrando bons resultados conforme os indicativos estatísticos MBE(%) = 0,25%, 0,51% e -0,38% e RMSE(%)= 5,78%, 9,83% e 12,93% para as coberturas de céu nublado, parcialmente nublado e aberto, respectivamente....

The present work presents an anisotropic correction model as a function of the clearness index (global/extraterrestrian radiation) for the diffuse radiation measurements with the Melo-Escobedo (ME) shadowring. Two statistical estimate models for the isotropic ( ) and anisotropic ( ) diffuse fraction as a function of clearness index are also proposed to estimate the hourly, daily and monthly diffuse irradiations. The global, diffuse measured by the shadowring ME and the direct radiations measurements were provided by the Laboratory of Solar Radiometry of UNESP/Botucatu/SP in the period from 1996 to 2002. The anisotropic correction model, obtained from the comparison between the diffuse irradiance measured by the Melo-Escobedo shadowring (radius of 40cm and width of 10cm) and the diffuse irradiance measured by the difference method (reference), considered three discreet intervals, with three equations: (0 < <0,30 - cloudy); (0,30 < <0,65 - partially cloudy); and (0,65 < <1 - clear). The anisotropic correction model was validated through the comparison of the anisotropic diffuse irradiance and the reference diffuse irradiance with an independent database, showing good results according to the statistical indicators MBE (%) = 0,25%, 0,51% and -0,38% and RMSE (%) = 5,78%, 9,83% and 12,93% for cloudy, partially cloudy and clear skies, respectively. The anisotropic correction model showed to be dependent of the shadowring dimensions, and for a same radius-width relationship, the smaller radius (20cm) and width (5cm) shadowring needed smaller numeric correction than the larger ray (40cm) and width (10cm) one. The anisotropic correction model was applied in the diffuse irradiance measurements obtained with a 5 minutes frequency automated operating system. The algorithm calculated hourly, daily and monthly anisotropic diffuse irradiations and compared to the ones from the reference diffuse ...(Complete abstract, access undermentioned eletronic address).
Keywords: Radiação solar; Métodos estatísticos; Anisotropia; Diffuse solar radiation; Measuring methods; Correction factors; Estimating models